(untitled) (Research, Society and Development, 2020)
Sugarcane wax (SCW) was fractionated using hot ethanol and a simple washout system, the obtained fractions soluble (SSCW) and insoluble (ISCW) were used to produce organogels crystallized at two different temperatures (5 and 25°C) at the concentrations of 1, 2, 3 and 4% (w/w). The laboratory research evaluated the behavior of organgels obtained from sugarcane wax (and its fractions), all organogels were assessed due to its microstructure, thermal behavior, rheological behavior and mechanical resistance. Samples were visually assessed for stability at a controlled temperature oven (at 5, 25 and 35°C), and the thermal behavior for SCW, SSCW and ISCW were different. The enthalpy variation changed from 118.87 to 129.63 and 85.65 J/g for the fractions. Organogels obtained from these materials were somewhat similar during crystallization (TPeak of 42.83, 37.19 and 36.23°C respectively), crystallization and melting enthalpy variation presented hysteresis as observed for other waxy organogels. SSCW organogels were significantly harder than the obtained with SCW and ISCW. Micrographs of the organogels showed a more organized network present on SSCW organogel when compared with SCW that was more organized than ISCW organogels. The difference on the microstructure observed explains the difference on the mechanical behavior of organogels formed with sugarcane wax hot ethanol-soluble and insoluble fractions.